2010
DOI: 10.1590/s0104-11692010000600006
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Musculoskeletal Disorders in Nursing Workers

Abstract: This cross-sectional study identified factors associated to musculoskeletal disorders in nursing auxiliaries and technicians in Salvador -Bahia. Three hundred and eight randomly selected female workers answered a questionnaire administered by an interviewer, with questions related to physical and psychosocial demands at work, individual characteristics and activities outside work. Multivariate analysis revealed that musculoskeletal disorders in neck, shoulder or upper back and musculoskeletal disorders in low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
1
12

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 13 publications
4
39
1
12
Order By: Relevance
“…The present study found a 75% prevalence of musculoskeletal discomfort among nurses who work at intensive care units, and it corroborates previous studies that also verified a high prevalence of the discomfort among nurses who work in hospital environments, including ICUs 22,23 . This high prevalence may be explained by factors that arise from work logistics in intensive care units.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study found a 75% prevalence of musculoskeletal discomfort among nurses who work at intensive care units, and it corroborates previous studies that also verified a high prevalence of the discomfort among nurses who work in hospital environments, including ICUs 22,23 . This high prevalence may be explained by factors that arise from work logistics in intensive care units.…”
Section: Discussionsupporting
confidence: 92%
“…It is known that this work place presents conditions that initiate stress, in addition to presenting environmental risk factors, work overload, and other biopsychophysiological consequences 26 . In fact, Fonseca and Fernandes 23 highlight that the physical aspects of work overload have an important contribution in the development of WRMD, especially in the upper limbs, such as inadequate posture and repetitive tasks. Nurses who work at ICUs perform tasks that demand physical effort, such as patient handling 27 , placing and removing monitors on and off shelves and cabinets, and equipment organization, besides the assignments related to patient care 26 .…”
Section: Discussionmentioning
confidence: 99%
“…These constitute an important public health problem in various industrialized countries and affect workers from a variety of professions (1) , including Nursing (2)(3)(4)(5)(6) .…”
Section: Introductionmentioning
confidence: 99%
“…As cargas fisiológicas podem estar relacionadas ao esforço físico realizado pelo trabalhador durante o desenvolvimento do trabalho, evidenciando-se a realização das atividades com posturas em pé, percorrendo longas distâncias dentro da instituição, além de fatores ergonômicos, como manipulação e levantamento de peso e posturas inadequadas (12,18,20,31) , assim como a realização do trabalho em turnos (35) , e o desenvolvimento do trabalho no turno noturno (9,15,25,30,38,40,(45)(46)51) .…”
Section: Categoria 2 -Condições De Trabalho Que Predispõem àS Cargas unclassified
“…As principais doenças, causas e notificações de afastamentos do trabalho são decorrentes do sistema osteoconjuntivo e tecido muscular (8) , osteoarticular e por traumas (23) , doenças do trato digestivo, oftalmológico e psíquico (25) , distúrbios osteomusculares (57) de região lombar, pescoço, ombro e parte alta do dorso e extremidades superiores distais e membros inferiores (18,20,22,25) , dor musculoesquelética (53) e dor nas costas (48) .…”
Section: Categoria 3 -Influências Das Cargas De Trabalho Na Saúde Do unclassified